Co-encapsulation of two plasmids in chitosan microspheres as a non-viral gene delivery vehicle. - (:unkn) unknown (CANADIAN SOC PHARMACEUTICAL SCIENCES, 2003)
Purpose. The aims of this study are to encapsulate two different plasmid DNAs (pGL2 and pMK3) in the same microsphere structure and to investigate in vivo transfection characteristics of chitosan microspheres. Furthermore, the effect of formulation factors, such as chitosan concentration and plasmid DNA amount on in vitro properties of microspheres were studied. Methods. Double plasmid-loaded chitosan microspheres were prepared by complex coacervation. Release studies were done in phosphate buffered saline at 37degrees C and released plasmid DNA was determined spectrophotometrically. Integrity of plasmid DNAs was checked by agarose gel electrophoresis. For in vivo transfection studies, microspheres were injected into the muscle of the mice and expression of proteins (beta-galactosidase and luciferase) was measured. Results. High encapsulation efficiency was obtained with chitosan microspheres (90%). The size of particles was about 1.15-1.28 mum. No dependence was observed between the size and formulation variables (chitosan concentration and the amount of plasmid). After encapsulation process, integrity of two plasmids did not change. Plasmid DNAs were continuously released from chitosan microspheres. Chitosan concentrations and plasmid amounts affected in vitro release properties. After intramuscular injection of double plasmids loaded microspheres into muscle of the mice, co-expression was obtained. High beta-galactosidase and luciferase productions were determined with these microspheres after a long post-transfection period (12 weeks). Conclusions. Our results showed that two plasmids could be encapsulated in chitosan microspheres without affecting their structural and functional integrity. Thus, sustained and high protein production was obtained with these microspheres.
Keywords: DNA; THERAPY